Counting the Pinocchios: The effect of summary fact-checking data on perceived accuracy and favorability of politicians - Alexander Agadjanian (Research & Politics, 2019)
Can the media effectively hold politicians accountable for making false claims? Journalistic fact-checking assesses the accuracy of individual public statements by public officials, but less is known about whether this process effectively imposes reputational costs on misinformation-prone politicians who repeatedly make false claims. This study therefore explores the effects of exposure to summaries of fact-check ratings, a new format that presents a more comprehensive assessment of politician statement accuracy over time. Across three survey experiments, we compared the effects of negative individual statement ratings and summary fact-checking data on favorability and perceived statement accuracy of two prominent elected officials. As predicted, summary fact-checking had a greater effect on politician perceptions than individual fact-checking. Notably, we did not observe the expected pattern of motivated reasoning: co-partisans were not consistently more resistant than supporters of the opposition party. Our findings suggest that summary fact-checking is particularly effective at holding politicians accountable for misstatements.